Clinical features, imaging findings and molecular data of limb-girdle muscular dystrophies in a cohort of Chinese patients - Feng Lin; Kang Yang; Xin Lin; Ming Jin; Long Chen; Fu-ze Zheng; Liang-liang Qiu; Zhi-xian Ye; Hai-zhu Chen; Min-ting Lin; Ning Wang; Zhi-qiang Wang (Orphanet Journal of Rare Diseases, 2023)
Abstract Background Limb-girdle muscular dystrophies (LGMDs) are a group of heterogeneous inherited diseases predominantly characterized by limb-girdle muscle weakness and dystrophic changes on histological analysis. The frequency of LGMD subtypes varies among regions in China and ethnic populations worldwide. Here, we analyzed the prevalence of LGMD subtypes, their corresponding clinical manifestations, and molecular data in a cohort of LGMD patients in Southeast China. Methods A total of 81 consecutive patients with clinically suspected LGMDs from 62 unrelated families across Southeast China were recruited for targeted next-generation sequencing and whole-exome sequencing from July 2017 to February 2020. Results Among 50 patients (41 families) with LGMDs, the most common subtypes were LGMD-R2/LGMD2B (36.6%) and LGMD-R1/LGMD2A (29.3%). Dystroglycanopathies (including LGMD-R9/LGMD2I, LGMD-R11/LGMD2K, LGMD-R14/LGMD2N and LGMD-R20/LGMD2U) were the most common childhood-onset subtypes and were found in 12.2% of the families. A total of 14.6% of the families had the LGMD-R7/LGMD2G subtype, and the mutation c.26_33dupAGGTGTCG in TCAP was the most frequent (83.3%). The only patient with the rare subtype LGMD-R18/LGMD2S had TRAPPC11 mutations; had a later onset than those previously reported, and presented with proximal‒distal muscle weakness, walking aid dependency, fatty liver disease and diabetes at 33 years of age. A total of 22.0% of the patients had cardiac abnormalities, and one patient with LMNA-related muscular dystrophy/LGMD1B experienced sudden cardiac death at 37 years of age. A total of 15.4% of the patients had restrictive respiratory insufficiency. Muscle imaging in patients with LGMD-R1/LGMD2A and LGMD-R2/LGMD2B showed subtle differences, including more severe fatty infiltration of the posterior thigh muscles in those with LGMD-R1/LGMD2A and edema in the lower leg muscles in those with LGMD-R2/LGMD2B. Conclusion We determined the prevalence of different LGMD subtypes in Southeast China, described the detailed clinical manifestations and distinct muscle MRI patterns of these LGMD subtypes and reported the frequent mutations and the cardiorespiratory involvement frequency in our cohort, all of which might facilitate the differential diagnosis of LGMDs, allowing more timely treatment and guiding future clinical trials.